Neoadjuvant immune checkpoint blockade triggers persistent and systemic Treg activation which blunts therapeutic efficacy against metastatic spread of breast tumors - Blomberg, Olga S.; Kos, Kevin; Spagnuolo, Lorenzo; Isaeva, Olga I.; Garner, Hannah; Wellenstein, Max D.; Bakker, Noor; Duits, Danique E.M.; Kersten, Kelly; Klarenbeek, Sjoerd; Hau, Cheei-Sing; Kaldenbach, Daphne; et al. (Oncoimmunology, 2023)
The clinical successes of immune checkpoint blockade (ICB) in advanced cancer patients have recently spurred the clinical implementation of ICB in the neoadjuvant and perioperative setting. However, how neoadjuvant ICB therapy affects the systemic immune landscape and metastatic spread remains to be established. Tumors promote both local and systemic expansion of regulatory T cells (T regs ), which are key orchestrators of tumor-induced immunosuppression, contributing to immune evasion, tumor progression and metastasis. T regs express inhibitory immune checkpoint molecules and thus may be unintended targets for ICB therapy counteracting its efficacy. Using ICB-refractory models of spontaneous primary and metastatic breast cancer that recapitulate the poor ICB response of breast cancer patients, we observed that combined anti-PD-1 and anti-CTLA-4 therapy inadvertently promotes proliferation and activation of T regs in the tumor, tumor-draining lymph node and circulation. Also in breast cancer patients, T reg levels were elevated upon ICB. Depletion of T regs during neoadjuvant ICB in tumor-bearing mice not only reshaped the intratumoral immune landscape into a state favorable for ICB response but also induced profound and persistent alterations in systemic immunity, characterized by elevated CD8+ T cells and NK cells and durable T cell activation that was maintained after treatment cessation. While depletion of T regs in combination with neoadjuvant ICB did not inhibit primary tumor growth, it prolonged metastasis-related survival driven predominantly by CD8+ T cells. This study demonstrates that neoadjuvant ICB therapy of breast cancer can be empowered by simultaneous targeting of T regs, extending metastasis-related survival, independent of a primary tumor response.